Microwave assisted multiwall carbon nanotubes enhancing Cd(II) adsorption capacity in aqueous media - Mubarak, N.M.; Sahu, J.N.; Abdullah, E.C.; Jayakumar, N.S.; Ganesan, P. (Elsevier, 2015)
Novel multiwall carbon nanotubes (MWCNTs) have been successfully synthesized using tubular microwave chemical vapour deposition technique and proved to be an outstanding adsorbent for the removal of Cd(II) from aqueous solution. The effect of process parameters such as pH, MWCNTs dosage, agitation speed and time were investigated. The maximum adsorption capacities of Cd(II) were found to be 88.62 mg/g and a statistical analysis reveals that the optimum conditions for the highest removal (98) of Cd(II) are at pH 5, MWCNTs dosage 0.1 g, agitation speed and time of 160 rpm and 50 min, respectively with the initial concentration of 10 mg/L. The Langmuir and Freundlich isotherm models match the experimental data very well and adsorption kinetic obeyed pseudo-second order. Our results proved that MWCNTs can be used as an effective Cd(II) adsorbent due to the high adsorption capacity as well as the short adsorption time needed to achieve equilibrium. (C) 2014 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.